Results of haploidentical transplant in patients with donor-specific antibodies: a survey on behalf of the Spanish Group of Hematopoietic Transplant and Cell Therapy - Bailén, Rebeca; Alenda, Raquel; Herruzo-Delgado, Beatriz; Acosta-Fleitas, Cynthia; Vallés, Ana; Esquirol, Albert; Fonseca, Marta; Solán, Laura; Sánchez-Vadillo, Irene; Bautista, Guiomar; Bento, Leyre; López-Godino, Oriana; et al. (Frontiers in Immunology, 2023)
Donor-specific antibodies (DSAs) are IgG allo-antibodies against mismatched donor HLA molecules and can cause graft failure (GF) in the setting of haploidentical hematopoietic stem cell transplantation (haplo-HSCT). Our aim was to report the experience of the Spanish Group of Hematopoietic Transplant (GETH-TC) in DSA-positive patients who had undergone haplo-HSCT. We conducted a survey of patients who underwent haplo-HSCT in GETH-TC centers between 2012 and 2021. Data were collected on the DSA assay used, monitoring strategy, complement fixation, criteria for desensitization, desensitization strategies and transplant outcomes. Fifteen centers from the GETH-TC responded. During the study period, 1,454 patients underwent haplo-HSCT. Seventy transplants were performed in 69 DSA-positive patients, all of whom lacked a suitable alternative donor; 61 (88%) patients were female (90% with prior pregnancies). All patients received post-transplant cyclophosphamide-based graft-versus-host disease prophylaxis. Regarding baseline DSA intensity, 46 (67%) patients presented mean fluorescence intensity (MFI) >5,000, including 21 (30%) with MFI >10,000 and three (4%) with MFI >20,000. Six patients did not receive desensitization treatment, four of them with MFI<5,000. Of 63 patients receiving desensitization treatment, 48 (76%) were tested after desensitization therapy, and a reduction in intensity was confirmed in 45 (71%). Three patients (5%) experienced an increase in MFI after desensitization, two of whom experienced primary GF. Cumulative incidence of neutrophil engraftment at day 28 was 74% in a median of 18 days (IQR, 15─20); six patients died before engraftment due to toxicity or infection and eight patients had primary GF despite desensitization in seven of them. After a median follow-up of 30 months, two-year overall and event-free survival were 46.5% and 39%, respectively. The two-year cumulative incidence of relapse was 16% and non-relapse mortality (NRM) was 43%. Infection was the most frequent cause of NRM, followed by endothelial toxicity. Multivariate analysis identified baseline MFI >20,000 as an independent risk factor for survival and an increase in titers after infusion as an independent risk factor for GF. Haplo-HSCT is feasible in DSA-positive patients, with high rates of engraftment after desensitization guided by DSA intensity. Baseline MFI >20,000 and increased intensity after infusion are risk factors for survival and GF.